Pendekatan Six Sigma Dengan Tahapan DMAI Terhadap Kualitas Pada Kemasan Gula - Putri, Ananda Hapsari; Wahyudi, Rizqi; Nugraha, Andhyka Tyaz (Teknoin, 2025)
The objective of this study is to compute the Defects Per Million Opportunities (DPMO) metric and the Sigma Level of the organisation. Additionally, the study attempts to identify the underlying variables contributing to defects and propose recommendations for enhancing the process. This study employs a Six Sigma methodology, incorporating the Define, Measure, Analyse, Improve and Control (DMAIC) stages. According to the findings derived from the analysis of the data, the mean value of the company's Defects Per Million Opportunities (DPMO) is 97, while the standard deviation (sigma) is calculated to be 5.26. Defects can arise due to a combination of human factors, processes, and machines. Enhancements are devised in accordance with the underlying cause of the failure mode exhibiting the highest Risk Priority Number (RPN) value. The findings derived from the Failure Mode and Effects Analysis (FMEA) indicate that the ripped packaging issue can be attributed to an inadequate approach employed in the preparation of refined sugar. This particular cause was assigned a Risk Priority Number (RPN) value of 384. The suggested enhancement at PT. AHP involves modifying either the dimensions of the pallet or the configuration of refined sugar on the pallet. The occurrence of loose sutures can be attributed to inconsistent sewing techniques, which has been assigned a Risk Priority Number (RPN) value of 336. The suggested course of action for PT. AHP involves implementing routine preventative maintenance measures and ensuring optimal working conditions for personnel in the packing area.